الطبيعة القانونيـــــة للحقـــــــوق العماليــــــــــــــة ( آمريــــة الحقوق العماليــــة ) - رشيد صبا نعمان; عبدالكريم سرى محي (Journal of Legal Sciences, 2019)
The features of the phenomenon in legal thinking in the modern era the employment rules of criminal law in the public and private a like punishment for the crime of the property protected by the civil law .